2021
DOI: 10.1101/2021.03.20.436259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acriflavine, a clinically aproved drug, inhibits SARS-CoV-2 and other betacoronaviruses

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 has been socially and economically devastating. Despite an unprecedented research effort, effective therapeutics are still missing to limit severe disease and mortality. Using high-throughput screening, we identified acriflavine as a potent papain-like protease (PLpro) inhibitor. NMR titrations and a co-crystal structure confirm that acriflavine blocks the PLpro catalytic pocket in an unexpected binding mode. We show that the drug inhibits viral replication at nanomol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We focused mainly on the drugs that went successfully through the MedChemExpress HY-138687). We have also included acriflavine 7 (SigmaAldrich; A8126), which we previously shown to be a potent ex vivo and in vivo inhibitor of betacoronaviruses blocking the PL pro protease. Further, remdesivir 8 sold by Gilead Sciences as Veklury by was included in the panel (polymerase inhibitor; GS-441524; Cayman Chemical, USA) and AT-527 developed by Atea Pharmaceuticals 9 (polymerase inhibitor; bemnifosbuvir hemisulfate; MedChemExpress HY-137958).…”
Section: Textmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused mainly on the drugs that went successfully through the MedChemExpress HY-138687). We have also included acriflavine 7 (SigmaAldrich; A8126), which we previously shown to be a potent ex vivo and in vivo inhibitor of betacoronaviruses blocking the PL pro protease. Further, remdesivir 8 sold by Gilead Sciences as Veklury by was included in the panel (polymerase inhibitor; GS-441524; Cayman Chemical, USA) and AT-527 developed by Atea Pharmaceuticals 9 (polymerase inhibitor; bemnifosbuvir hemisulfate; MedChemExpress HY-137958).…”
Section: Textmentioning
confidence: 99%
“…The infection was carried out for 72 h, and the cytopathic effect (CPE) was assessed. Culture supernatants were collected for analysis, which was carried out as previously described 7 . The experiment was performed in three biological repetitions, each in duplicate (n=6).…”
Section: Textmentioning
confidence: 99%
“…CPI-169 was tested at 0.5 mM in 6% DMSO-d 6 ; GRL-0617 at 0.3 mM in 6% DMSO-d 6 . The assignment of 1 H and 13 C chemical shifts for CPI-169 and GRL-0617 was performed using 2D experiments, including 1 H-1 H TOCSY with mixing time of 0.02 s, 1 H-13 C HSQC, and 1 H-1 H tr-NOESY experiments. 1D 1 H STD experiments [27] were performed with different concentrations while the protein:compound ratio remained 1:100.…”
Section: Nmrmentioning
confidence: 99%
“…It has been shown to bind close to the catalytic site but not to occupy it [12]. The compound acriflavine was reported to be a potent nanomolar inhibitor of SARS-CoV-2 PLpro in enzymatic, cell based and in-vivo studies [13]. Using NMR and crystal structure of PLpro it was shown that two proflavine molecules occupy the substrate binding pocket.…”
Section: Introductionmentioning
confidence: 99%